Síntese, caracterização e avaliação de hidrogéis superabsorventes copolimerizados empregados na liberação lenta de fertilizantes - Macedo, Osmir Fabiano Lopes de (2022)
In this study, a new series of superabsorbent hydrogels composed of polyacrylamide (pAAm), cellulose acetate (CA), and montmorillonite (MMT) suitable for slow release of fertilizers were synthesized and their synergistic effects were evaluated through sorption and desorption studies of nitrogen fertilizer, urea (CO(NH2)2). The results for the degree of swelling show a 60% increase in weight at pH 6.0 when varying from 5 to 10% of MMT in the hydrogel composition. The presence of montmorillonite and cellulose acetate in the hydrogel caused the system to release the nutrient in a more controlled manner than with the pure hydrogel. Soil water retention showed that the synthesized hydrogels retain up to 39% more water when compared to soil without hydrogel and release in times of up to 30 days. The hydrogels showed a low percentage of applied nitrogen recovery (about 42% less than the treatment with urea), demonstrating the efficiency in reducing nitrogen leaching losses. The measures of urea release in the soil (25%, 75% and 89% in 5, 20 and 30 days), presented by the hydrogel "C" (pAAm/10% MMT/10% CA) were gradual and indicated a slow release behavior. When applied to the lettuce crop, it was found that it favored improvements in all variables studied when compared to the control. In conclusion, excellent results were obtained for the controlled desorption of urea, highlighting the hydrolyzed hydrogels containing 10% montmorillonite and 10% cellulose acetate. The total nutrient values show that this material is potentially viable for application in agriculture.